Prevalence of Perceived Stress and Mental Health Indicators Among Reserve-Component and Active-Duty Military Personnel - Lane, Marian E. (American Public Health Association, 2012)
Objectives. We examined stress levels and other indicators of mental health in reservists and active-duty military personnel by deployment status. Methods. We used data from the Department of Defense Health-Related Behaviors surveys, which collect comprehensive, population-based data for reserve and active-duty forces. Data were collected from 18 342 reservists and 16 146 active-duty personnel. Results. Overall, with adjustment for sociodemographic and service differences, reservists reported similar or less work and family stress, depression, and anxiety symptoms than did active-duty personnel. However, reservists who had been deployed reported higher rates of suicidal ideation and attempts than did active-duty personnel who had been deployed and higher rates of post-traumatic stress disorder symptomatology than did any active-duty personnel and reservists who had not been deployed. The highest rates of suicidal ideation and attempts were among reservists who had served in theaters other than Iraq and Afghanistan. Conclusions. Our results suggest that deployment has a greater impact on reservists than on active-duty members, thus highlighting the urgent need for services addressing reservists’ unique postdeployment mental health issues. Also, deployment to any theater, not only Iraq or Afghanistan, represents unique threats to all service members’ mental well-being.